Comparing BSEM and EUPD Estimates for Two-Group SB-MTMM Experiments. Issue 5 (3rd September 2019) - Saris, Willem E.; Satorra, Albert
Abstract : In 2018, two different approaches have been suggested to solve the estimation problems that have been detected during the analysis of the data of the two-group split ballot multi-trait multi-method (SB-MTMM experiments performed in many countries between 2002 and 2010 in the European Social Survey). One group suggested using the Bayesian estimation. The other group suggested a new estimation procedure (EUPD) that makes use of the pooled data across the different countries. In this note, we present a comparison of the results of the two approaches on the same generated data, which are comparable with the data that created problems in the ESS.